(Dys)functional art. (1st September 2014) - Priglinger, Sabine; Sever, Hande; Schmechel, Ben
This article aims to explore the binary of art as a functional cultural tool and as a dysfunctional sociopolitical catalyst. The authors, Hande Sever, Sabine Priglinger and Ben Schmechel, will propose dysfunctional art as a generator of an emancipatory, intentional space of enquiry, a valuable alternative to the more functional notions of art. They will stress that dysfunctional works of art span a range of artistic production and reception as they occur in both commercial gallery and community or public space. Instances that embody elements of the functional and the dysfunctional approach will be marked out through an interrogation of artworks, arranged in an atemporal, ahistorical constellation.